A Long-Term Longitudinal Examination of the Effect of Early Onset of Alcohol and Drug Use on Later Alcohol Abuse. Issue 4 (October 2015) - Ohannessian, Christine McCauley; Finan, Laura J.; Schulz, Jessica; Hesselbrock, Victor
Background: Early onset of alcohol use has been linked to later alcohol problems in adulthood. Currently, it is not clear whether early onset of marijuana and tobacco use similarly predicts alcohol problems. Moreover, most studies examining the effect of early substance use onset on later problems only have followed youth into their early 20s. Therefore, the primary goal of this study was to examine whether early onset of alcohol, marijuana, and tobacco use predicts alcohol problems beyond the transition to adulthood. Methods: The sample included 225 15–19-year-old youth (60% girls; 62% Caucasian) who were surveyed in three time periods: 1993–1998 (Time 1), 1998–2003 (Time 2), and 2003–2007 (Time 3). Participants reported their age of onset for regular drinking, tobacco use, and marijuana use. At each time of measurement, they also completed surveys relating to their alcohol use and abuse. Results: Participants with an earlier age of onset of drinking regularly scored higher on the Michigan Alcoholism Screening Test (MAST) and drank more frequently to get high and drunk throughout their 20s. Tobacco use onset and marijuana use onset were not associated with later alcohol use or abuse. Conclusions: Results from this study suggest that the relationship between the onset of substance use and later substance abuse may be substance specific. Of note, early onset of regular drinking was associated with alcohol problems during adulthood, underscoring the importance of delaying the onset of regular alcohol use among youth.